2015
DOI: 10.1186/s40555-015-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosability and description of a new subspecies of Indo-Pacific humpback dolphin, Sousa chinensis (Osbeck, 1765), from the Taiwan Strait

Abstract: Background: Subspecies recognition can affect how people (scientists and non-scientists alike) view organisms and thus has important implications for research on, as well as the conservation of, these entities. Recently, a small group of Indo-Pacific humpback dolphins was discovered inhabiting the waters off central western Taiwan. This geographically isolated population possesses pigmentation patterns that are subtly, but noticeably, different from their nearest conspecifics in the neighbouring waters of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
(99 reference statements)
0
24
0
Order By: Relevance
“…), and differential color pattern demonstrated the presence of a new subspecies of Indo‐Pacific humpback dolphin ( Sousa chinensis taiwanensis ) in Taiwan (Wang et al . ). Skull morphology differentiation and low mitochondrial gene flow between Tursiops truncatus from the Black Sea and the Mediterranean Sea supported the presence of the distinct subspecies T. t. ponticus in the Black Sea (Viaud‐Martinez et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), and differential color pattern demonstrated the presence of a new subspecies of Indo‐Pacific humpback dolphin ( Sousa chinensis taiwanensis ) in Taiwan (Wang et al . ). Skull morphology differentiation and low mitochondrial gene flow between Tursiops truncatus from the Black Sea and the Mediterranean Sea supported the presence of the distinct subspecies T. t. ponticus in the Black Sea (Viaud‐Martinez et al .…”
Section: Discussionmentioning
confidence: 97%
“…Several cetacean subspecies have been described using morphological differentiation. For example, a subspecies of spinner dolphin (Stenella longirostris roseiventris) was recognized in Southeast Asian waters based on morphological characters (Perrin et al 1999), and differential color pattern demonstrated the presence of a new subspecies of Indo-Pacific humpback dolphin (Sousa chinensis taiwanensis) in Taiwan (Wang et al 2015). Skull morphology differentiation and low mitochondrial gene flow between Tursiops truncatus from the Black Sea and the Mediterranean Sea supported the presence of the distinct subspecies T. t. ponticus in the Black Sea (Viaud-Martinez et al 2008).…”
Section: Taxonomy Of the Genus In The Western South Atlantic Oceanmentioning
confidence: 99%
“…The critically endangered population inhabiting the eastern Taiwan Strait (TWD), designated as S. chinensis taiwanensis (Wang et al . ), consists of ~74 individuals (Wang et al . ).…”
Section: Numbers Of Previously Identified Females and Males In The Prmentioning
confidence: 99%
“…The population inhabiting the Pearl River Estuary (PRE) in China (including Hong Kong) consists of~2,500 individuals and 200-300 photo-identified animals are regularly sighted in Hong Kong waters (Dungan et al 2012). The critically endangered population inhabiting the eastern Taiwan Strait (TWD), designated as S. chinensis taiwanensis (Wang et al 2015), consists of~74 individuals . Numerous anthropogenic threats, such as vessel traffic, fisheries, and pollution (Jefferson et al 2009, Ross et al 2010, cause concern about the viability of the PRE population (Jefferson et al 2012) and the possible extirpation of TWD (Ara ujo et al 2014).…”
mentioning
confidence: 99%
“…Among humpback dolphin populations, those that inhabit the waters along the western coast of Taiwan (WTC, also described as the eastern Taiwan Strait) have recently been designated a separate subspecies (Wang, Yang, & Hung, ) and classified as critically endangered (Wang, Araujo‐Wang, Perrin, & Braulik, ; Wang et al, ) because of the small population size (Wang, Yang, Fruet, Daura‐Jorge, & Secchi, ; Wang, Yang, Hung, & Jefferson, ) and low viability (Huang et al, ) in an intensely impacted environment (Karczmarski et al, ; Ross et al, ; Slooten et al, ; Wang, Araujo‐Wang, et al, ; Wang et al, ). HPA zoning for this subspecies has been proposed (Chou et al, ; Liu, Wang, Chuang, & Chen, ; Ross et al, ), but this has not yet been implemented.…”
Section: Introductionmentioning
confidence: 99%